Jurisdição em rede para porcos-espinhos: a necessidade de instituição da tese da resposta correta na estrutura do Estado Democrático de Direito - Schalanski, Mariana Tonico (2019)
This research aims to establish bases to allow the construction of correct answers This research aims to establish bases to allow the construction of correct answers in Law - good answers, hermeneutically adequate to the Constitution from a democratic theory of legal decision. To this end, it will be argued that a legally and democratically correct decision must have its legitimacy confirmed in two ways: first, by following a procedure in which the (constitutionally appropriate) participation of all stakeholders is guaranteed, Dworkin calls it moral participation; second, by legal decisions responsible to the integrity of the law. The proposal that best meets the requirements of a legal decision as a democratic issue will be the Hedgehog Network Jurisdiction, which in turn aims to build a coherent unit in which it must respect its being as integrity; This is the gateway to the formulation of the hermeneutic circle of meanings that preserves the fundamental right of members of the political community to guarantee a coherent decision based on principles that provide the best justification for legal practice as a whole.